Estrutura familiar e estilos parentais em diferentes configurações familiares - Nora, Cristina Dalla (2018)
Changes in the conception of the family are observed, however, its importance for the development of the individual in its psychosocial aspects is undeniable. The family configuration gained diversity and plurality, while the traditional model no longer presents itself as the only group perceived as family. Given the importance of understanding families more and more, this study aimed to understand the exercise of family function in different settings in the psychosocial formation of adolescents. Three main instruments were used to collect data: a) parental styles scale, with the evaluation of two dimensions: parental responsiveness and demandingness; b) family climate inventory, considering the factors of cohesion, support, hierarchy and conflict; c) structured family interview, to understand the family interactions in its structure. The results showed that the four family systems, with different configurations, exercised their role and function in the formation of the individual and facilitated the promotion of the emotional health of their members, even with differences in their educational practices and family interactions. However, it was the family systems conceived by affective bonds and cohabitation that demonstrated better results in the dimensions and factors studied, which pointed to more functional family systems.